2014
DOI: 10.1177/0021955x14525796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stearic acid/organic montmorillonite on EVA/SA/OMMT nanocomposite foams by melting blending

Abstract: The effects of stearic acid (SA)/organic montmorillonite (OMMT) on the morphology and mechanical properties of nanocomposite foams based on ethylene vinyl acetate (EVA) copolymer were studied. The dispersion of montmorillonite layers was characterized by both X-ray diffraction and transmission electron microscopy. The cellular microstructure of the foamed samples was observed by scanning electron microscope. The effects of SA/OMMT on the mechanical properties of the EVA-based foams were also investigated. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Generally, four methods for the fabrication of the polymeric foam with CCS had been reported, which were co-blowing agent method [1][2][3], two-step depressurization method [4][5][6][7][8], polymer blending system method [9][10][11][12][13], as well as cooling and depressurization method [14]. Polystyrene (PS) foams with CCS were prepared using water and n-butane as co-blowing agents in extrusion and it was found that the CCS could be tuned by n-butane/water/silica content and die temperature [2].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, four methods for the fabrication of the polymeric foam with CCS had been reported, which were co-blowing agent method [1][2][3], two-step depressurization method [4][5][6][7][8], polymer blending system method [9][10][11][12][13], as well as cooling and depressurization method [14]. Polystyrene (PS) foams with CCS were prepared using water and n-butane as co-blowing agents in extrusion and it was found that the CCS could be tuned by n-butane/water/silica content and die temperature [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the dimorphism on the size between nanometric and micrometric agglomerated particles, the formation of a bimodal foam is favored. By increasing the cellulose fiber content, the probability of obtaining agglomerated particles is higher, as well as the probability of obtaining a bimodal foam . Figure shows the variation of the arrangement of the CN in the EVA foams.…”
Section: Resultsmentioning
confidence: 98%
“…However, considering the data shown in Figure , by increasing the CN content, the presence of large cells increases, and on the contour of these large cells the presence of a large amount of small cells is observed. Foams with the presence of two different groups of cells, that is, of two sizes, is discussed by Duan et al . and are defined as bimodal foams.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPE can be defined as a class of polymers, which combines the properties of rubbers with the processing ease of thermoplastics . Among thermoplastics, ethylene‐vinyl acetate copolymer (EVA) is a polymer which has properties intermediate to those of its two constituent homopolymers, namely, polyethylene and poly(vinyl‐acetate) . Styrene‐butadiene rubber (SBR) is a general purpose synthetic rubber that presents high filler‐loading capacity, good flex resistance, crack‐initiation resistance, and abrasion resistance .…”
Section: Introductionmentioning
confidence: 99%